Black Barrio on the Border: "Blaxicans" of Ciudad Juárez, Mexico. Issue 1 (1st January 2020) - Campbell, Howard; Williams, Michael
ABSTRACT: Typically, analysts perceive the U.S.-Mexico border in terms of brown and white, that is, as the place where Mexican and (White) American cultures both come together as well as divide and conflict. Although the standard emphases are beginning to change, there is still a dearth of studies of border people of African descent. The article concerns a Black barrio in Ciudad Juárez, Chihuahua, Mexico, that existed from the 1950s to the 1990s. The life of Jerome Brown, a leader of the historical Juárez "Blaxican" neighborhood, forms the center of the article, which is supplemented by interviews and ethnographic observations concerning this exceptional and fascinating border community. The Juárez "Blaxicans" created an international solution (joining a society in Mexico that was less racist toward them) to the national problem of white racism in the U.S. Besides documenting the community, this article examines the community's significance in terms of theorizing about the roles of race, ethnicity and nation in a border context in which two distinct, yet often intertwined, race/ethnic/color systems operate. This article also contributes to research on expatriate minorities, a relatively understudied topic, especially in relation to scholarship on migration, ethnography and borders.